Gene Conversion Between Cationic Trypsinogen (PRSS1) and the Pseudogene Trypsinogen 6 (PRSS3P2) in Patients with Chronic Pancreatitis. Issue 3 (13th March 2015) - Rygiel, Agnieszka Magdalena; Beer, Sebastian; Simon, Peter; Wertheim‐Tysarowska, Katarzyna; Oracz, Grzegorz; Kucharzik, Torsten; Tysarowski, Andrzej; Niepokój, Katarzyna; Kierkus, Jarosław; Jurek, Marta; Gawliński, Paweł; Poznański, Jarosław; et al.
ABSTRACT: Mutations of the human cationic trypsinogen gene ( PRSS1 ) are frequently found in association with hereditary pancreatitis. The most frequent variants p.N29I and p.R122H are recognized as disease‐causing mutations. Three pseudogene paralogs in the human trypsinogen family, including trypsinogen 6 ( PRSS3P2 ), carry sequence variations in exon 3 that mimic the p.R122H mutation. In routine genetic testing of patients with chronic pancreatitis, we identified in two unrelated individuals similar gene conversion events of 24–71 nucleotides length between exon 3 of the PRSS1 (acceptor) and PRSS3P2 (donor) genes. The converted allele resulted in three nonsynonymous alterations c.343T>A (p.S115T), c.347G>C (p.R116P), and c.365_366delinsAT (p.R122H). Functional analysis of the conversion triple mutant revealed markedly increased autoactivation resulting in high and sustained trypsin activity in the presence of chymotrypsin C. This activation phenotype was identical to that of the p.R122H mutant. In addition, cellular secretion of the triple mutant from transfected HEK 293T cells was increased about twofold and this effect was attributable to mutation p.R116P. Our observations confirm and extend the notion that recombination events between members of the trypsinogen family can generate high‐risk PRSS1 alleles. The pathogenic phenotype of the novel conversion is explained by a unique combination of increased trypsinogen activation and secretion.